Prevention of Renal Injury After Induction of Ozone Tolerance in Rats Submitted to Warm Ischaemia. Issue 1 (1999) - Barber, E.; Menéndez, S.; León, O. S.; Barber, M. O.; Merino, N.; Calunga, J. L.; Cruz, E.; Bocci, V.
Abstract : On the basis that ozone (O3 ) can upregulate cellular antioxidant enzymes, a morphological, biochemical and functional renal study was performed in rats undergoing a prolonged treatment with O3 before renal ischaemia. Rats were divided into four groups: (1) control, a medial abdominal incision was performed to expose the kidneys; (2) ischaemia, in animals undergoing a bilateral renal ischaemia (30 min), with subsequent reperfusion (3 h); (3) O3 + ischaemia, as group 2, but with previous treatment with O3 (0.5 mg/kg per day given in 2.5 ml O2 ) via rectal administration for 15 treatments; (4) O2 + ischaemia, as group 3, but using oxygen (O2 ) alone. Biochemical parameters as fructosamine level, phospholipase A, and superoxide dismutases (SOD) activities, as well as renal plasma flow (RPF) and glomerular filtration rate (GFR), were measured by means of plasma clearance of p-amino-hippurate and inulin, respectively. In comparison with groups 1 and 3, the RPF and GFR were significantly decreased in groups 2 and 4. Interestingly, renal homogenates of the latter groups yielded significantly higher values of phospholipase A activity and fructosamine level in comparison with either the control (1) and the O3 (3) treated groups. Moreover renal SOD activity showed a significant increase in group 3 without significant differences among groups 1, 2 and 4. Morphological alterations of the kidney were present in 100%, 88% and 30% of the animals in groups 2, 4 and 3, respectively. It is proposed that the O3 protective effect can be ascribed to the substantial possibility of upregulating the antioxidant defence system capable of counteracting the damaging effect of ischaemia. These findings suggest that, whenever possible, ozone preconditioning may represent a prophylactic approach for minimizing renal damage before transplantation.